Utilization of Atomic Nucleus Fission Reactions in Energy Conversion Systems of Nuclear Power Plants - Jamaluddin, Indah Hamdhani; Karnila; Greys, Priskilya; Utami, Ni Wayan Mega Savira (Physics Department, Faculty of Mathematics and Natural Sciences, Universitas Negeri Makassar, 2025)
This research aims to review scientific articles that are relevant and related to the utilization of atomic nucleus fission reactions in energy conversion systems in Nuclear Power Plants (NPPs) and the environmental impact of radioactive waste management. The research method used in writing this article is literature review. The literature search focused on the keywords “nuclear fission reaction”, “nuclear power plant energy conversion”, and “radioactive waste”, resulting in a total of 15 articles and 2 book. Based on the results of the literature review analysis, it is concluded that: (a) The atomic nucleus fission reaction is the main basis for energy production in nuclear power plants with high efficiency. (b) The energy conversion system in nuclear power plants involves thermodynamic processes and turbine-generators to convert heat energy into electricity. (c) Radioactive waste management requires advanced technology and strict policies to minimize environmental impact. (d) NPPs has great potential as a clean energy source, but the main challenge lies in handling nuclear waste and reactor safety.